Melacak Kemajuan Pemikiran Filsafat Masa Daulah Abbasiyah - Fikri, Muslim; Mawardi, Kholid (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2023)
Philosophy always evolves over time. This relates to human critical thinking which is always interesting to learn. Philosophical thought, in this case Islamic philosophy, is based on the progress of thought during the time of the Abbasid State, at which time there was a large-scale translation of Greek classics. Some of the greatest philosophers namely al-Kindi, al-Farabi, Ibn Sina, Ibn Rushd, and others contributed to the greatness of Islamic philosophical thought. Therefore, this article aims to describe and analyze the development of philosophical thought produced during the Abbasid State. This research was conducted using the literature method, looking for articles related to the topic. This type of research is a library research using qualitative descriptive methods. The steps taken by researchers in reviewing this research include collecting sources, commenting on sources, interpreting, and writing results. Philosophical thought in Islam produces thoughts about the concept of soul or reason, metaphysics, prophethood, morals or ethics, and the philosophy of happiness as the key and direction in solving life's problems.